Design and demonstration of adiabatic quantum-flux-parametron logic circuits with superconductor magnetic shields. (13th March 2015) - Inoue, Kenta; Takeuchi, Naoki; Narama, Tatsuya; Yamanashi, Yuki; Yoshikawa, Nobuyuki
Abstract: Adiabatic quantum-flux-parametron (AQFP) logic is an energy-efficient superconductor logic with zero static power and very small dynamic power due to adiabatic switching operations. In order to build large-scale digital circuits, we built AQFP logic cells using superconductor magnetic shields, which are necessary in order to avoid unwanted magnetic couplings between the cells and excitation currents. In preliminary experimental tests, we confirmed that the unwanted coupling became negligibly small thanks to the superconductor shields. As a demonstration, we designed a four-to-one multiplexor and a 16-junction full adder using the shielded logic cells. In both circuits, we confirmed correct logic operations with wide operation margins of excitation currents. These results indicate that large-scale AQFP digital circuits can be realized using the shielded logic cells.